Effect of Energy/Protein Ratio and Strain on Performance, Nutrient Digestibility and Serum Biochemical Indices of Exotic and Locally Adapted Turkey - Akinsuyi M.A. (International Journal of Biochemistry and Biomolecule Research, 2023)
This study investigated the response of locally adapted and exotic turkeys raised under the same environmental conditions to diets with varying energy/protein ratio. One hundred and fourty-four (144) four-week old poults of each strain of turkey were randomly selected and assigned to six different diets in a 2 x 2 x 3 factorial arrangement. Each treatment diet were replicated twice with twelve (12) birds per replicate. Diets formulated with 28 %, 26 % and 24 % crude proteins levels were distributed to energy levels 2900 kcal/kg and 3000 (Kcal/Kg) with six energy/ protein (E/P) ratio 104:1, 112:1, 121:1, 107:1, 115:1, 125:1 respectively were fed to turkeys from 4 to 8 weeks. At 7th week of age, 2 birds per replicate were randomly selected and put in digestibility cages. Feacal samples collected from birds on daily basis for five days were weighed on wet and dry basis to determine the moisture and dry matter content. Body weight changes were recorded for the trial. The strain effect significantly (P<0.05) influenced the final body weight, daily weight gain, and daily feed intake in this trial. A significant strain x energy/protein interaction effect was observed on the final body weight. Energy/protein significantly (P<0.05) influenced the digestibility of crude fibre, ether extract, and ash. There was significant (P<0.05) effect of strains and E/P ratios on serum creatinine level. It is concluded that different energy protein ratios are required for optimum performance of exotic turkey (112:1) and locally adapted turkey (115:1) in the tropics.
Keywords: Locally adapted; digestibility; energy/protein ratio; exotic; serum; strain